Immunohistochemistry with Anti-BRAF V600E (VE1) Mouse Monoclonal Antibody is a Sensitive Method for Detection of the BRAF V600E Mutation in Colon Cancer: Evaluation of 120 Cases with and without KRAS Mutation and Literature Review - Dvorak, Katerina (Pathol Oncol Res, 2017)
The major aim of this study was to evaluate the performance of anti-BRAF V600E (VE1) antibody in colorectal tumors with and without KRAS mutation. KRAS and BRAF are two major oncogenic drivers of colorectal cancer (CRC) that have been frequently described as mutually exclusive, thus the BRAF V600E mutation is not expected to be present in the cases with KRAS mutation. In addition, a review of 25 studies comparing immunohistochemistry (IHC) using the anti-BRAF V600E (VE1) antibody with BRAF V600E molecular testing in 4041 patient samples was included. One-hundred and twenty cases with/without KRAS or BRAF mutations were acquired. The tissue were immunostained with anti-BRAF V600E (VE1) antibody with OptiView DAB IHC detection kit. The KRAS mutated cases with equivocal immunostaining were further evaluated by Sanger sequencing for BRAF V600E mutation. Thirty cases with BRAF V600E mutation showed unequivocal, diffuse, uniform, positive cytoplasmic staining and 30 cases with wild-type KRAS and BRAF showed negative staining with anti-BRAF V600E (VE1) antibody. Out of 60 cases with KRAS mutation, 56 cases (93.3%) were negative for BRAF V600E mutation by IHC. Four cases showed weak, equivocal, heterogeneous, cytoplasmic staining along with nuclear staining in 25–90% of tumor cells. These cases were confirmed to be negative for BRAF V600E mutation by Sanger sequencing. Overall, IHC with anti-BRAF V600E (VE1) antibody using recommended protocol with OptiView detection is optimal for detection of BRAF V600E mutation in CRC. Our data are consistent with previous reports indicating that KRAS and BRAF V600E mutation are mutually exclusive.